2018
DOI: 10.1155/2018/6718083
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatics Approach for Epitope-Based Peptide Vaccine Design and Active Site Prediction against Polyprotein of Emerging Oropouche Virus

Abstract: Oropouche virus (OROV) is an emerging pathogen which causes Oropouche fever and meningitis in humans. Several outbreaks of OROV in South America, especially in Brazil, have changed its status as an emerging disease, but no vaccine or specific drug target is available yet. Our approach was to identify the epitope-based vaccine candidates as well as the ligand-binding pockets through the use of immunoinformatics. In this report, we identified both T-cell and B-cell epitopes of the most antigenic OROV polyprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 96 publications
1
87
0
1
Order By: Relevance
“…A lower IC 50 value indicates higher binding affinity of the epitopes with the MHC class I and II molecules. While most of the studies 24, 25 reported that a binding affinity (IC 50 ) threshold of 250 nM identifies peptide binders recognized by T-cells, and this threshold can be used to select peptides, we kept binding affinity within 50 nM to get better confidence level in predicting epitopes for MHC-I and MHC-II alleles. The IEDB MHC-I prediction tool retrieved 77 T-cell epitopes in RBD that interacted with 21 possible MHC-I alleles whereas the NTD domain possessed 35 T-cell epitopes with 17 possible MHC-I alleles (Supplementary Data 1).…”
Section: Resultsmentioning
confidence: 99%
“…A lower IC 50 value indicates higher binding affinity of the epitopes with the MHC class I and II molecules. While most of the studies 24, 25 reported that a binding affinity (IC 50 ) threshold of 250 nM identifies peptide binders recognized by T-cells, and this threshold can be used to select peptides, we kept binding affinity within 50 nM to get better confidence level in predicting epitopes for MHC-I and MHC-II alleles. The IEDB MHC-I prediction tool retrieved 77 T-cell epitopes in RBD that interacted with 21 possible MHC-I alleles whereas the NTD domain possessed 35 T-cell epitopes with 17 possible MHC-I alleles (Supplementary Data 1).…”
Section: Resultsmentioning
confidence: 99%
“…143,144 In another example, sequence analysis of Lassa fever virus (the LASV) and other viruses' immunoproteomic was used to identify the best immunogenic protein predicting T-cell as well as B-cell epitopes and also target sequence and binding sites. 145,146 The SSNLYKGVY peptide sequence at AA41-49 of glycoprotein 1 (produced by the L segment) was the best candidate epitope for the induction of humoral as well as the cell-mediated immunity for Lassa fever vaccine construct. 17 HLA-I and 16 HLA-II molecules have been proven in sizable African populations and their combination with the SSNLYKGVY peptide sequence may prove useful in such Lassa fever virus endemic areas.…”
Section: The Subpopulation Levelmentioning
confidence: 99%
“…The distribution and expression of HLA alleles vary according to the ethnicities and regions throughout the world (Adhikari, Tayebi, and Rahman 2018), thus, influence the successful development of an epitope-based vaccine ). The population coverage by the designed vaccine was calculated with the IEDB Population Coverage tool .…”
Section: Estimation Of Population Coveragementioning
confidence: 99%